MENINGKATKAN KINERJA BISNIS MELALUI KEUNGGULAN BERSAING KULINER KHAS SEMARANG (StudiPada Sentra Usaha MikroLumpia, Bandeng Presto danWingko di Kota Semarang) - Bogy Febriatmoko; Susilo Toto Raharjo (Conference In Business, Accounting, And Management (CBAM), 2015)
This research analyze the effect of entrepreneurship orientation, market orientation, and competitive advantage to enhance the business performance. This research  formula is how to create competitive advantage to enhance the business performance.  The population which has selected in this research is micro business cluster of lumpia, bandeng presto, and wingko in Semarang. Those are 104 industries and total sample of this research are 102 industries. Collecting data using questionnaire with score start from 1 (very disagree at all) to 7 (strongly agree at all). The data analysis tool which used is Structural Equation Modelling (SEM) with AMOS 18.  The result  of the data  analysis  goodness of fit index shows that  the research  model has  the suitability of fit (acceptable).  Not  all  hypothesis can  be  accepted  after  SEM analysis.  Accepted hypothesis  is  the  effect of entrepreneurship   orientation   on  business  performance,  market  orientation   on  competitive  advantage,   and competitive advantage  on business performance. While the rejected hypothesis is the effect of entrepreneurship orientation on competitive advantage and market orientation on business performance.  Generally,  the conclusion from the result  of testing model which applied  to micro business cluster  of lumpia, bandeng  presto,  and  wingko in Semarang  shows that  competitive advantage  can  be achieved through  market orientation, where competitive advantage which resulted by the firm can enhance the business performance. This research provides some research limitation and future research agenda that can be done to further research.  Keywords:  entrepreneurship   orientation,   market  orientation,   competitive  advantage,   business  performance